2013
DOI: 10.1016/j.canlet.2013.06.012
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA ‘signature’ during estrogen-mediated mammary carcinogenesis and its reversal by ellagic acid intervention

Abstract: Dysregulated miRNA expression has been associated with the development and progression of cancers, including breast cancer. The role of estrogen (E2) in regulation of cell proliferation and breast carcinogenesis is well-known. Recent reports have associated several miRNAs with estrogen receptors in breast cancers. Investigation of the regulatory role of miRNAs is critical for understanding the effect of E2 in human breast cancer, as well as for developing strategies for cancer chemoprevention. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 47 publications
(90 reference statements)
4
48
0
2
Order By: Relevance
“…In the present study, it was demonstrated that treatment with E2 significantly enhanced the viability, migration and invasion of ERα-positive breast cancer cells. Previously, Munagala et al used the August-Copenhagen Irish rat model, which develops mammary tumors by E2 treatment, to investigate changes in miRs during the process of mammary tumorigenesis, and found that several miRs, such as miR-375, -206, -182, -122, -127 and -183, were dysregulated throughout the mammary carcinogenesis process (24). These findings suggest that certain miRs are involved in the development of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was demonstrated that treatment with E2 significantly enhanced the viability, migration and invasion of ERα-positive breast cancer cells. Previously, Munagala et al used the August-Copenhagen Irish rat model, which develops mammary tumors by E2 treatment, to investigate changes in miRs during the process of mammary tumorigenesis, and found that several miRs, such as miR-375, -206, -182, -122, -127 and -183, were dysregulated throughout the mammary carcinogenesis process (24). These findings suggest that certain miRs are involved in the development of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[302] p57, Bax and caspase-3 miR-206 is a potent tumor supressor p57 and Bax upregulated, and cleaved caspase-3 protein upregulated ACI model rat mammary tissue [308] Actin-like 6A (BAF53a), a subunit of the SWI/SNF chromatin remodeling complex Elevated BAF53a Downregulation of miR-206 Primary rhabdomyosarcoma tumors [309] Actin-like 6A (BAF53a) BAF53a transcript is significantly higher in primary rhabdomyosarcomas than in normal muscle…”
Section: Myomirs and Cancermentioning
confidence: 99%
“…Furthermore, treatment with E2 has previously been found to cause deregulation of many miRs during the mammary carcinogenesis process (30), suggesting that miRs may play a role in breast cancer. For instance, miR-125b was found to be significantly upregulated in breast cancer, and its upregulation was associated with poor prognosis and aromatase inhibitor resistance (31).…”
Section: Discussionmentioning
confidence: 99%